Discovery of Amurinocellia H. Aspöck & U. Aspöck (Raphidioptera: Inocelliidae) in China, with description of two new species - Liu, Xingyue; Aspöck, Horst; Yang, Ding; Aspöck, Ulrike (Zootaxa, 2009)
The snakefly genus Amurinocellia (Raphidioptera: Inocelliidae) is recorded from China for the first time. Two species are described as new to science: Amurinocellia sinica sp. nov. and Amurinocellia australis sp. nov. A new combination, Amurinocellia calida (H. Aspöck & U. Aspöck) comb. nov. is proposed. A key is provided for the species of Amurinocellia. The generic status and the zoogeography of Amurinocellia are discussed.